Fostering self-regulation and life science-technical-vocational integrated skills through career-focused teaching - Honra, Joelash R. (College of Education, University of the Philippines Diliman, 2020)
This study was conducted to assess the effectiveness of career-focused teaching (CFT) compared to the science conventional teaching (SCT) approach in enhancing students’ self-regulation (SR) and life science-technical-vocational integrated skills (LSTVIS). Specifically, it sought to find out if students exposed to CFT showed significant improvement on their SR and LSTVIS than those students exposed to SCT, and if SR was a significant positive predictor of LSTVIS. The study followed the quasi-experimental pretest-posttest non-equivalent groups design. Two instruments were administered as both pretest and posttest in the study: the Self-Regulation Questionnaire (SRQ) was used to evaluate students’ initiative and responsibility in acquiring knowledge, and a researcher-made instrument, Life Science-Technical-Vocational Integrated Skills Questionnaire (LSTVISQ) was used to evaluate their perception on the skills that both Life Science and technical-vocational education have to be applied by the students in creating their knowledge products as guided by CFT. The mean pretest scores in SRQ and LSTVISQ were subjected to a two-tailed independent samples t-test to establish the initial comparability of the two groups prior to the intervention. The sample of the study consisted of two intact sections of Grade 11 TVL Animation students in a public high school institution in Makati City who were enrolled in Earth and Life Science during the first semester of the School Year 2019-2020. Seventy students served as the respondents, 35 of them were in the CFT class and the other 35 students were in the SCT class. Both classes were taught by the researcher. The study found out that students in the CFT class showed significant improvement on their self-regulation and life science-technical-vocational integrated skills compared to those who were in the SCT class as revealed by the mean posttest ratings analyzed using independent samples t-test. Also, it was found out that self-regulation is a predictor of life science-technical-vocational integrated skills. Thus, the CFT was proven effective in enhancing students' SR and (LSTVIS) in life science. Furthermore, self regulation positively predicts students' life science-technical-vocational integrated skills in CFT class. This study therefore recommends the integration of career-focused teaching in the other subjects and tracks in the senior high school. Also, it recommended that the approach be incorporated in the curriculum of life science and the implementation phase be done for a longer duration in case this study is replicated.